ANALYSIS OF OPPORTUNITIES AND THE CURRENT STATUS OF INCREASING THE EFFICIENCY OF THE USE OF LABOR RESOURCES IN THE REPUBLIC OF UZBEKISTAN - Rasulov Shavkat Sharof uglu (Scholar Express Journals, 2022)
In this article, labor resources, their formation and economic role are theoretically investigated. And also, the difference between labor resources, based on their specific features, is justified. The current state of the use of labor resources in Uzbekistan is analyzed and economically justified proposals and recommendations are developed for their effective use in the future
Keywords: Labor Resources; Labor Market; Employment; Economic Active Population